Using Game-Based Virtual Classroom Simulation in Teacher Training: User Experience Research. (April 2021) - Kelleci, Özge; Aksoy, Nuri Can
Background: Simulation-based training is an effective, and therefore increasingly widespread, tool used in the teaching and assessment of complex skills. In order to determine the effectiveness of thevirtual classroom simulators used in teacher training, there is a need for studies intouser experiences, within the scope ofhuman-computer interaction, which provide an indicator of software usability. Aim: The aim of this study was to examine the experiences ofteacher candidates andacademics in the use of SimInClass, agame-based virtual classroom simulator . Method: 16 senior teacher candidates and two academics, determined by the criterion sampling method, participated in the case study which involved a focus group interview, one-on-one interviews, and observation techniques. The case study centered around a 14-weekteacher training program which used theSimInClass simulation . Data related to user experiences was analyzed independently by two researchers, and the fit index between the data encoders was calculated as being 0.94. Results and Conclusion: The participants who preferred to use theSimInClass simulation on a computer said they did so because of user input, usage control and screen size, while those who favored using a mobile device pointed to the easy access. All of the participants felt that theSimInClass simulation was effective in providing clear directions and giving feedback. One suggestion was that the simulation should give clues regarding the correct solution, while some users felt that it needed to be made more accessible for different disciplines. Despite some reservations and suggestions of this type, the overall impression of the test subjects was that the use ofvirtual classroom simulators inteacher training was effective.